Advantages of Low Partial Pressure of Oxygen Processing of Alkali Niobate: NaNbO3. Issue 6 (4th February 2014) - Shimizu, Hiroyuki; Kobayashi, Keisuke; Mizuno, Youichi; Randall, Clive A.; Brennecka, G. L.
<x xml:space="preserve">Abstract</x> This work focused on the processing of low oxygen partial pressure (low‐pO2) calcination and sintering with respect to NaNbO3 (NN) of one key member in ferroelectric (Na, K)NbO3. The high‐density NN ceramics were successfully prepared without any sintering additives using the low‐pO2 process. Comparing conventional air process, the low‐pO2 calcined NN powders showed lower defect concentration and higher densification. The low‐pO2 sintered NN ceramics had dielectric constant and dielectric loss performance at high temperatures. Furthermore, the low‐pO2 sintered NN ceramics indicated ferroelectric behavior, and both maximum polarization and strain improved to two to three times that of conventional air‐sintered NN ceramics. From this relatively simple compound, NN, the advantage of low‐pO2 is unambiguously demonstrated and points to its consideration. It is hypotheses as a kinetically controlled process that limits the volatility under low‐pO2 condition.